WHAT MOVES THE MARKET? EXPLORING FACTORS THAT SHAPE INVESTOR BEHAVIOUR IN EQUITIES (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2025)
With rapid changes in the perspective of the stock market as well as investors’ behavior, the financial market has become organized. Various stock markets in all over India are opened for trading. In the last few decades, the major focus is diverted towards the study of investors’ behavior. The main intent of this study is to develop a broader understanding about investors’ psychological behavior for the purpose of increasing the efficiency of individual investors as well as the market. Investments of investors contribute funds not only in the capital market but also in the growth of the economy. This study is an attempt to analyze the behavioral factors which include different types of biases as well as big five personality traits that influence their investment decisions.
Keywords: Personality traits; Behavioral factors; Biases; Investment Decisions